Estudio agroclimatológico - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
The main activity consisted of climatic data base validation and error correction. A sensitive technique of error detection was developed, based on the relative amplitudes of the high and low frequencies of the Fourier transform. The Bean Program desired to obtain a characterization and listing of areas susceptible to anthracnose (Colletotrichum lindemuthianum) attack, including production figures. To do so, an alternative method was chosen of defining climatic limits for the disease. A growing season temp. between 17-22 degrees Celsius and a daily rainfall of 1.5 mm/day were chosen. Total at-risk bean production amounts to 57 percent of the total target area production. Growth habits of Phaseolus vulgaris are briefly described and accessions of Phaseolus referred to in this report are listed. (CIAT)